Influence of high-concentration LLDPE on the manufacturing process and morphology of pitch/LLDPE fibres - Aldosari, Salem Mohammed; Khan, Muhammad A.; Rahatekar, Sameer S. (MDPI, 2021)
A high modulus of elasticity is a distinctive feature of carbon fibres produced from mesophase pitch. In this work, we expand our previous study of pitch/linear low-density polyethylene blend fibres, increasing the concentration of the linear low-density polyethylene in the blend into the range of from 30 to 90 wt%. A scanning electron microscope study showed two distinct phases in the fibres: one linear low-density polyethylene, and the other pitch fibre. Unique morphologies of the blend were observed. They ranged from continuous microfibres of pitch embedded in linear low-density polyethylene (occurring at high concentrations of pitch) to a discontinuous region showing the presence of spherical pitch nodules (at high concentrations of linear low-density polyethylene). The corresponding mechanical properties—such as tensile strength, tensile modulus, and strain at failure—of different concentrations of linear low-density polyethylene in the pitch fibre were measured and are reported here. Thermogravimetric analysis was used to investigate how the increased linear low-density polyethylene content affected the thermal stability of linear low-density polyethylene/pitch fibres. It is shown that selecting appropriate linear low-density polyethylene concentrations is required, depending on the requirement of thermal stability and mechanical properties of the fibres. Our study offers new and useful guidance to the scientific community to help select the appropriate combinations of linear low-density polyethylene/pitch blend concentrations based on the required mechanical property and thermal stability of the fibres.
Keywords: winder; morphology; carbon-fibres; polyethylene; mesophase-pitch